An Evaluation of Health Policy Implementation for Hajj Pilgrims in Indonesia - Rustika Rustika; Ratih Oemiati; Al Asyary; Tety Rachmawati (Springer, 2020)
Background: For last decades, the mortality rate of hajj pilgrims from Indonesia was between 2.1 and 3.2 per 1000 hajj pilgrims. At the same time, morbidity affected 87% of the elderly (>65 years old), of which 83% faced high risk of health problems. This is a complex problem affecting hajj health care in Indonesia. The study was aimed to understand what extent of the hajj implementation on health care in Indonesia. Methods: This review was conducted by abstracting of three studies in Indonesian hajj health care. Two of the studies were based on cross-sectional reviews, while one was a case-control study. The majority of the studies performed laboratory tests to evaluate the disease conditions among hajj pilgrims through secondary data. Results: First study presented that hajj Posbindu (integrated post-coaching) was not functional in managing the health problems of the pilgrims. It shows that the stroke prevalence is 10.9 per 1000 people, Diabetes Mellitus (DM) 10.9% of the people, and coronary heart disease 1.5%. The second study expressed that, according to health isthitaah (policy implementation), there were 20% hajj pilgrims who delayed their trip because of health issues. Most of them had chronic kidney disease, dementia, or lung tuberculosis. The policy implementation of health isthitaah was not smooth; there was little collaboration between the Ministry of Health and Ministry of Religious Affairs, and the population was not sufficiently educated in the area, resulting in hajj pilgrims with poor knowledge, attitude, and practice in health isthitaah. This notion was enforced in the third study. Conclusion: The coaching according to health isthitaah should be encouraged alongside collaboration between the Ministry of Health and Ministry of Religious Affairs. Socialization in public health has to increase according to health isthitaah, which can be done by district health centers.